2007
DOI: 10.1093/ndt/gfm598
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal haemodialysis increases pharyngeal size in patients with sleep apnoea and end-stage renal disease

Abstract: Conversion from CHD to NHD is associated with an increase in pharyngeal cross-sectional area. This may play a role in some patients whose sleep apnoea improves on NHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 33 publications
2
59
0
6
Order By: Relevance
“…Beecroft et al (19) recently showed that pharyngeal narrowing contributes to the pathogenesis of OSA in dialysis-dependent patients. Furthermore, in patients converted from conventional to nocturnal hemodialysis, there was an increase in pharyngeal size together with improvement in sleep apnea (20). This study is the first to show a reduction in airway diameter on conversion from NPD to CAPD.…”
Section: Discussionmentioning
confidence: 52%
“…Beecroft et al (19) recently showed that pharyngeal narrowing contributes to the pathogenesis of OSA in dialysis-dependent patients. Furthermore, in patients converted from conventional to nocturnal hemodialysis, there was an increase in pharyngeal size together with improvement in sleep apnea (20). This study is the first to show a reduction in airway diameter on conversion from NPD to CAPD.…”
Section: Discussionmentioning
confidence: 52%
“…56 Furthermore, changes in the pharyngeal cross-sectional area was assessed after conversion from conventional hemodialysis (4 h/day, 3 days/week) to nocturnal hemodialysis (8 h/night, 3-6 nights/week) in 24 ESRD patients, of whom 16 had AHI ≥ 15/h (predominantly obstructive). 57 There were significant increases in the average pharyngeal cross-sectional area at functional residual capacity (3.29 cm 2 vs 3.39 cm 2 ) and at residual volume (1.91 cm 2 vs 2.13 cm 2 ) (p < 0.05) after conversion to nocturnal hemodialysis, with a 19% (3 of 16) response rate (AHI reduced to 15/h) in apneic patients.…”
Section: Pharyngeal Narrowingmentioning
confidence: 88%
“…Other mechanism include reduction in lung volume secondary to pulmonary edema, especially during sleep, which can reduce the upper airway size. 57 Finally, uremic myopathy or neuropathy can directly affect the upper airway dilator muscles and so reduce the airway size, [60][61] although this mechanism has not been investigated in patients with ESRD.…”
Section: Pharyngeal Narrowingmentioning
confidence: 99%
“…115 This group also reported an improvement in pharyngeal size among nocturnally dialyzed patients. 117 This may improve sleep apnea and consequently ambulatory BP. Another mechanism of BP reduction with frequent dialysis is suggested to be an increase in arterial compliance and consequently improvement in baroreflex sensitivity.…”
Section: Frequent Dialysis and Its Effect On Bpmentioning
confidence: 99%